Discovery of novel small molecule inhibitors of cardiac hypertrophy using high throughput, high content imaging. (August 2016) - Reid, Brian G.; Stratton, Matthew S.; Bowers, Samantha; Cavasin, Maria A.; Demos-Davies, Kimberley M.; Susano, Isidro; McKinsey, Timothy A.
Abstract: Chronic cardiac hypertrophy is maladaptive and contributes to the pathogenesis of heart failure. The objective of this study was to identify small molecule inhibitors of pathological cardiomyocyte hypertrophy. High content screening was performed with primary neonatal rat ventricular myocytes (NRVMs) cultured on 96-well plates and treated with a library of 3241 distinct small molecules. Non-toxic hit compounds that blocked hypertrophy in response to phenylephrine (PE) and phorbol myristate acetate (PMA) were identified based on their ability to reduce cell size and inhibit expression of atrial natriuretic factor (ANF), which is a biomarker of pathological cardiac hypertrophy. Many of the hit compounds are existing drugs that have not previously been evaluated for benefit in the setting of cardiovascular disease. One such compound, the anti-malarial drug artesunate, blocked left ventricular hypertrophy (LVH) and improved cardiac function in adult mice subjected to transverse aortic constriction (TAC). These findings demonstrate that phenotypic screening with primary cardiomyocytes can be used to discover anti-hypertrophic lead compounds for heart failure drug discovery. Using annotated libraries of compounds with known selectivity profiles, this screening methodology also facilitates chemical biological dissection of signaling networks that control pathological growth of the heart. Highlights: High throughput screening with primary cardiomyocytes Phenotypic screening with primary cardiomyocytes Small molecular library screening with primary cardiomyocytes Novel inhibitors of cardiac hypertrophy